2018
DOI: 10.31803/tg-20180312141348
|View full text |Cite
|
Sign up to set email alerts
|

Instructional design in game based learning and applications used in educational systems

Abstract: The paper examines literature on the subject of instructional design and game based learning with the aim of identifying its positive effects and impact on users. Special attention was given to learning, encouragement and development of skills acquired through the use of game based learning. Game based learning is considered to be a complex system that requires instructional support geared towards stimulating cognitive processes. Several empirical research papers which provide insight into this field of intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
2
5
0
1
Order By: Relevance
“…Finally, letters and words in the RG were often displayed in combination with oral support (i.e., modality principle; see also Mayer, 2014), while in the NSG numbers and numerosity were only printed. These three characteristics or instructional support in the RG are in line with the literature suggesting that game features such as feedback, interactivity and modality are beneficial for learner outcomes (Vusić et al, 2018).…”
Section: Socio-economic Status (Ses)supporting
confidence: 79%
See 1 more Smart Citation
“…Finally, letters and words in the RG were often displayed in combination with oral support (i.e., modality principle; see also Mayer, 2014), while in the NSG numbers and numerosity were only printed. These three characteristics or instructional support in the RG are in line with the literature suggesting that game features such as feedback, interactivity and modality are beneficial for learner outcomes (Vusić et al, 2018).…”
Section: Socio-economic Status (Ses)supporting
confidence: 79%
“…However, counterevidence for this first explanation is the fact that numerical comparison is identified as a predictor of math competence (Schneider et al, 2017) and that our general math competence tests also comprised comparison tests. Second, it might be possible that the integrated instructional support in each game is also partly responsible for the more positive results on reading compared to math (Vusić et al, 2018). In the RG children were able to follow their own proficiency through the game and were rewarded with a star after each finished subgame, two game features that were not present in the NSG.…”
Section: Socio-economic Status (Ses)mentioning
confidence: 99%
“…Pendekatan pembelajaran inovatif tersebut adalah pembelajaran berbasis permainan (game-based learning). Game-based learning merupakan sebuah sistem yang diterapkan dalam proses pendidikan, dimana pengguna (dosen) dapat mengadopsi sebuah permainan untuk kebutuhan minat kognitif dan motivasi belajar (Vusić, Bernik, & Geček, 2018). Connoly berpendapat (Stiller & Schworm, 2019), game-based learning berarti menggunakan permainan dalam konteks pendidikan untuk mencapai tujuan pendidikan.…”
Section: Pendahuluanunclassified
“…A study has reported that educational games could enhance student's learning interest and motivation (Burguillo, 2010). Game -based learning is a system which is being increasingly applied in the educational process and which has been clearly evidenced in a number of scientific papers that have been published over the past decade (Vusic and Gecek, 2018). Teachers prefer games not only in motivating students but also in the presentation and discussion of their lesson because students are actively participating if they will play a game.…”
Section: Sometimesmentioning
confidence: 99%